2019
DOI: 10.1002/trtr.1828
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Planning for Technology in Literacy Instruction

Abstract: Teachers often encounter barriers as they attempt to integrate digital technology into their literacy instruction, but developing a long-term plan can help teachers sustain their integration efforts over time.J amie (all names are pseudonyms) is a kinder garten teacher who believes that integrating technology into her literacy instruction is impor tant. However, like many teachers, she has had very little training in how to do so and has therefore had very little success. Stacy, a middle school language arts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…On one hand, the principals of the upper and lower 30% performing schools rated lowest respectively the items on the use of email or network to communicate with other Science teachers, with 2.3 and 1.8, and the use of a computer database to keep an inventory of Science equipment, supplies, references, audiovisual materials, with 2.3 and 1.9. The result presented that these things were practiced occasionally by the principals or at most 40% of the time (Attawell, 2009;Woodward and Beschorner, 2019). Moreover, the principals from the upper 30% frequently integrated technology in Science instruction at least 70% of the time as indicated by their over-all mean rating of 2.55.…”
Section: On the Level Of Implementation Of The Upper And Lower 30% Pe...mentioning
confidence: 96%
“…On one hand, the principals of the upper and lower 30% performing schools rated lowest respectively the items on the use of email or network to communicate with other Science teachers, with 2.3 and 1.8, and the use of a computer database to keep an inventory of Science equipment, supplies, references, audiovisual materials, with 2.3 and 1.9. The result presented that these things were practiced occasionally by the principals or at most 40% of the time (Attawell, 2009;Woodward and Beschorner, 2019). Moreover, the principals from the upper 30% frequently integrated technology in Science instruction at least 70% of the time as indicated by their over-all mean rating of 2.55.…”
Section: On the Level Of Implementation Of The Upper And Lower 30% Pe...mentioning
confidence: 96%
“…Elementary teachers worldwide expressed their struggles with pivoting to virtual instruction without adequate time or support (Fauzi & Khusuma, 2020;Schleicher, 2020). Before the pandemic, educators often felt unprepared to integrate technology into their instruction in meaningful ways (Beschorner & Woodward, 2019), which could be related to limited training in implementing instructional technology (Schleicher, 2020). During the pandemic, educators also noted their limited training.…”
Section: Time and Supportmentioning
confidence: 99%
“…Research conducted prior to the global pandemic has indicated that many educators have little to no professional development and technological support in distance education from their schools and districts (Beschorner & Woodward, 2019 ). This gap in technological training has become more apparent—largely due to the unforeseen nature of the pandemic—which has led educators around the world to scramble to meet their students’ learning needs during a crisis (Bozkurt & Sharma, 2020 ).…”
Section: Introductionmentioning
confidence: 99%